Bio-Imaging of Colorectal Cancer Models Using Near Infrared Labeled Epidermal Growth Factor - Cohen, Gadi; Lecht, Shimon; Arien-Zakay, Hadar; Ettinger, Keren; Amsalem, Orit; Oron-Herman, Mor; Yavin, Eylon; Prus, Diana; Benita, Simon; Nissan, Aviram; Lazarovici, Philip (PLOS ONE, 2012)
Novel strategies that target the epidermal growth factor receptor (EGFR) have led to the clinical development of monoclonal antibodies, which treat metastatic colorectal cancer (mCRC) but only subgroups of patients with increased wild type KRAS and EGFR gene copy, respond to these agents. Furthermore, resistance to EGFR blockade inevitably occurred, making future therapy difficult. Novel bio-imaging (BOI) methods may assist in quantization of EGFR in mCRC tissue thus complementing the immunohistochemistry methodology, in guiding the future treatment of these patients. The aim of the present study was to explore the usefulness of near infrared-labeled EGF (EGF-NIR) for bio-imaging of CRC using in vitro and in vivo orthotopic tumor CRC models and ex vivo human CRC tissues. We describe the preparation and characterization of EGF-NIR and investigate binding, using BOI of a panel of CRC cell culture models resembling heterogeneity of human CRC tissues. EGF-NIR was specifically and selectively bound by EGFR expressing CRC cells, the intensity of EGF-NIR signal to background ratio (SBR) reflected EGFR levels, dose-response and time course imaging experiments provided optimal conditions for quantization of EGFR levels by BOI. EGF-NIR imaging of mice with HT-29 orthotopic CRC tumor indicated that EGF-NIR is more slowly cleared from the tumor and the highest SBR between tumor and normal adjacent tissue was achieved two days post-injection. Furthermore, images of dissected tissues demonstrated accumulation of EGF-NIR in the tumor and liver. EGF-NIR specifically and strongly labeled EGFR positive human CRC tissues while adjacent CRC tissue and EGFR negative tissues expressed weak NIR signals. This study emphasizes the use of EGF-NIR for preclinical studies. Combined with other methods, EGF-NIR could provide an additional bio-imaging specific tool in the standardization of measurements of EGFR expression in CRC tissues.